Morphology of Platinum Electrodeposits in the Three-Dimensional Sublayer to Full Layer Range Produced under Different Potential Modulations on Highly Oriented Pyrolytic Graphite - Rodríguez Nieto, F. J. (2006)
The topography of platinum electrodes produced by electrodeposition (19 to 200 mC cm-2) on highly oriented pyrolytic graphite (HOPG) under different potential modulations was investigated by atomic force microscopy, scanning tunneling microscopy, and H-atom electrosorption voltammetry. To modulate electrodeposition, (i) triangular potential cycling at 0.1 V s-1, (ii) a linear cathodic potential at 0.1 V s-1 and anodic potential step cycling, and (iii) square wave potential cycling at 5000 Hz were utilized. AFM and STM imaging showed that at lower platinum loading the HOPG surface was partially covered by a 3D sublayer of platinum. Electrodes produced by procedure (i) were made of faceted platinum aggregates of about 200 nm and nanoclusters in the range of 5−20 nm; those that resulted from procedure (ii) consisted of anisotropic aggregates of nanoclusters arranged as quasi-parallel domains. These electrodes from (i) and (ii) behaved as fractal objects. The electrodes resulting from procedure (iii) exhibited a flat surface that behaved as a Euclidean object. For all WEs, as the platinum loading was increased the HOPG surface was fully covered by a thin 3D layer of platinum aggregates produced by electrodeposition and coalescence phenomena. Large platinum loading led to electrodes with fractal geometry. Statistical parameters (root-mean-square height, skewedness, kurtosis, anisotropy, Abbot curve, number of protrusions and valleys, and fractal dimension) were obtained from the analysis of AFM and STM imaging data. Platinum electrodeposition coupled to either H-adatom formation for procedures (i) and (ii) or phonon dispersion for (iii) was involved in the surface atom rearrangements related to electrofaceting. The H-adatom electrosorption voltammetry data were used to evaluate the real electrode surface area via the voltammetric charge and to advance a tentative explanation of the contribution of the different crystallographic facets to the global electrochemical process dominated by weak H−Pt adsorption interactions.